Colorectal Cancer Diagnosis, Screening and Management - Chen, Jindong (IntechOpen, 2018)
With international experts sharing their experience and knowledge on these different aspects in the management of colorectal cancer, this book has this opportunity to offer all physicians treating colorectal cancer, as well as researchers, updated information concerning the biology, diagnosis, screening, and treatment of colorectal carcinoma. This book provides a detailed evaluation of diagnostic modalities, in-depth analysis of screening for colorectal cancer, recent advances in treatment, and principles and trends in the management of colorectal cancer. This updated knowledge will be an interesting and informative read for any clinician involved in the management of patients with colorectal cancer. In addition, readers such as related physicians, researchers, and colorectal cancer patients are potential beneficiaries of this book.